Indigenous religion(s) – in the making and on the move: Sámi activism from Alta to Standing Rock - Kraft, Siv Ellen (Taylor & Francis, 2020)
This chapter explores the shift to ‘indigeneity’ and ‘indigenous religion’ among the Sámi, through a focus on Sámi activism at Alta (1979–1981, concerning a proposed power plant) and Standing Rock (2016–2017, concerning a proposed pipeline). It is based on a combination of multi-sited fieldwork, interviews and textual sources, and proceeds along the lines of ‘light comparison’, inspired partly by the comparative logic of indigeneity and indigenous religion. Kraft’s comparison is ‘light’ in the sense of few cases, contextually rich descriptions, and a primarily inductive and explorative approach. While partial, limited and centred on a few of the thousands of people involved in the protests this design provides windows into the broader stories to which the cases belong, across the 50-year timeline that separates them, and in different parts of an increasingly connected indigenous geography. It enables a comparative approach to indigenous religion as it has emerged and developed in Sámi contexts, across time, and the ways in which contexts shape performances and translations.